Incorporation of GeoGebra Applets and ChatGPT to Strengthen the Learning of Exact Equations in Engineering Students - Funes, Jorge Olivares; Parada, Byron Droguett; Julian, Pablo Martin de; Villegas, Alexandra Burgos (Mathematics and Computer Science: Contemporary Developments Vol. 7, 2024)
This paper presents the integration of GeoGebra applets and ChatGPT artificial intelligence in the learning of exact differential equations in the university context. GeoGebra has established itself as a powerful tool in teaching mathematical concepts, thanks to its ability to dynamically visualize and model, which facilitates deeper understanding and motivates the students. Meanwhile, ChatGPT provides detailed solutions, and step-by-step explanations that complement autonomous learning and reinforce mathematical problem-solving. The combination of GeoGebra and ChatGPT creates a dynamic learning environment that not only supports the visualization and experimentation of complex concepts, but also promotes interaction, offering an alternative to the traditional pencil-and-paper approach. This integration is especially relevant for engineering students in differential equations and multivariable calculus courses, as it provides a more comprehensive and effective learning experience, enhancing both their theoretical and practical skills.